Charlotte Brontë : Legacies and afterlives - Wynne, Deborah, 1963-; Regis, Amber K. (Interventions: rethinking the nineteenth century (Series), 2017)
"Charlotte Brontë: Legacies and Afterlives is a timely reflection on the persistent fascination and creative engagement with Charlotte Brontë's life and work. The new essays in this volume, which cover the period from Brontë's first publication to the twenty-first century, explain why her work has endured in so many different forms and contexts. This book brings the story of Charlotte Brontë's legacy up to date, analysing the intriguing afterlives of characters such as Jane Eyre and Rochester in neo-Victorian fiction, cinema, television, the stage and, more recently, on the web. Taking a fresh look at 150 years of engagement with one of the best-loved novelists of the Victorian period, from obituaries to vlogs, from stage to screen, from novels to erotic makeovers, this book reveals the author's diverse and intriguing legacy. Engagingly written and illustrated, the book will appeal to both scholars and general readers." --